EVALUASI PENERAPAN SISTEM PENGENDALIAN INTERNAL ATAS PENERIMAAN, PENGEMBALIAN DAN PELELANGAN BARANG JAMINAN PADA PT. PEGADAIAN (PERSERO) - Siwu, Fifke Masyie; Poputra, Agus T. (Universitas Sam Ratulangi, 2017)
PT. Pegadaian (Persero) provides loans to people with require collateral item as insurance. PT. Pegadaian have to keep the collateral save and maintain it secure, so that internal control for collateral items are necessary needed. The purpose of this research was to determine and evaluate the implementation of the internal control systems for receiving, returns, and auctions of collateral items at PT. Pegadaian (Persero). The method used is qualitative descriptive with five components of COSO to evaluate the effectivities of internal control that applied at PT. Pegadaian (Persero). The five components of the COSO internal control is the control environment, risk assessment, control activities, information and communication and monitoring. The results showed that internal control systems at PT. Pegadaian (Persero) have been support by Standard Operating Procedures for all operations and filed documents. But from the evaluation for internal control system of receiving, returns, and auctions of collateral items there are still task stacking at unit manager make internal control systems PT. Pegadaian (persero) still have lack of control.Keywords: Internal Control Systems, Collateral Item, COSO.